Remembering the spirit of the Beothuk : The Beothuk Saga of Bernard Assiniwi - Premat, Christophe (Stockholm University, 2020)
The paper was presented at the 20 th International Baltic Conference on Canadian Studies (10 October, 2020, Vilnius University) and deals with the historical novel of Bernard Assiniwi, The Beothuk Saga. Bernard Assiniwi was a well-known writer of the First Nations whose masterpiece was a historical novel written in French in 1996, The Beothuk Saga (Assiniwi, 2000) . Divided into three parts (The initiate, the invaders and the genocide), Assiniwi incorporates oral stories in the written genre of historical novels. The aim of the novel is both ethnological and cultural as the author presents the history of a nation that was destroyed by colonizers with the help of rival clans. By introducing a chronology on the history of this nation, Assiniwi adds a literary style to enlighten the cultural specificity of the Beothuk. Some researchers in native studies focused on the role of ethnopoetics (Feld, 1982) in order to catch the language and the spirit of the First Nations, whereas others prefer to introduce a form of comparative poetology (Miner, 1990; Beaujour, 2017: 19). The comparative poetology avoids the ethnocentric illusion and opens the possibility of translating and understanding the cultural and artistic productions of the First Nations. Hence, the historical novel is an interesting genre as it contributes to collect fragments of oral traditions into a continuous narrative. Unlike comparative poetology, the focus is on how the author re-members some important actions from unknown ancestors to describe a forgotten genealogy. By using the concept of “remembering” (Premat, Sule, 2016), the present presentation shows how the story of the Beothuks echoes an ancient tradition of Icelandic and Nordic sagas . Assiniwi rediscovers some important features of the first novels to give a voice to this nation.It seems that Assiniwi describes an ancient form of métissage that was possible in the genealogy of the Beothuks. In the previous studies on The Beothuk Saga, the hybridity of the narrative was analyzed as well as the founding myths (Jeannotte, 2010; Gatti, 2010). The author wanted to tell the story of the Beothuk from the native point of view. Gerald Vizenor, a native American Indian, described the characteristics of an unilateral colonial narrative that is taken as a historical truth in Western societies. “The Heirs of Christopher Columbus created one more New World in their stories and overturned the tribal prophecies that their avian time would end with the arrival of the white man. The heirs warm the stones at the tavern with their stories in the blood” (Vizenor, 1991: 5). Assiniwi expresses the desire of creating a counter-narrative of the indigenous communities (Bhabha, 1994: 66) by revealing the details of their ways of living and thinking. Moreover, by being inspired by the origins of the novel, Assiniwi reverses the aesthetic canons of the literary colonial tradition. The remembering process is all the deeper as it reintegrates parts of the colonial traditions. Assiniwi is one of the few native writers that adopted the historical novel to tell the story and the tragedy of the Beothuk. The origin of the novel is reused to transmit stories from the oral tradition as if the Beothuk’s story was not that different from other early European nations (Robert, 1988). Some of the characters embody this sense of living memory, just like the old man that inaugurates the second part of the novel. “He was the clan’s Living Memory, charged with keeping the past alive; he had been instructed to do this by his ancestor Anin, the first Beothuk to travel around the whole land now occupied by the Beothuk Nation” (Assiniwi, 2000: 137).To address this hypothesis, the presentation will focus on the ethnological tradition concerning the description of Beothuk. There were a few works made on the description of this Nation that can be compared with the details that Assiniwi give (Marshall, 1998: 240). The exogenous tradition has to be presented in order to contextualize the originality of Assiniwi’s work. Second, the genealogy of the ancestors will be studied in terms of lineages and métissage. They are connected to the spiritual drives of the environment which is quite hostile. The characters identify themselves with the natural elements, but the magical realism is never lyric in the novel. As the psychoanalyst Carl Gustav Jung explains it: “all the contents of our unconscious are constantly being projected into our surroundings, and it is only by recognizing certain properties of the objects as projections or imagos that we are able to distinguish them from the real properties of the objects” (Jung 1986, 50). The relation between the spiritual drives and the genealogy of the clan structures the first part of the novel. Third, the style of the saga will be analyzed (rhythm / characters / narrative focus / symbols / languages). There is no idealization of the ancestors but the rhythm is decisive in the way the chronology meets the story of the ancestors. The chronology is linear whereas the story of the ancestors follows the natural cycle. “For the first time since he had set out on his journey of initiation, Anin was undecided. Should he cross the forest in the direction shown to him by Woasut, to rejoin his people, or should he continue and complete his circumnavigation of their land, as he had given his word he would do?” (Assiniwi, 2000: 27). The notion of rythmanalysis is here adapted to focus on the alternation between the cyclical time and the historical time of the colonizers. In a nutshell, Assiniwi used the historical novel to make the reader enter into a new imaginary world and to understand the beliefs, the dreams and the thinking of this former Nation.